Postural comfort of driver works space in vehicle package design geometry: A pilot study on malaysian drivers in sedan car and MPV - Zuli'zam, R.; Nooh, A.B.; Ghazilla, R.A.R. (Malaysian Public Health Specialists Association, 2016)
The study of driver posture and comfort in driver workspace is important in vehicle package design especially in two different type of vehicle, sedan and Multi-Purpose Vehicle (MPV). Due to different seat position in the driver workspace, investigation of driver accommodation in relations to driver anthropometry is essential to ensure its meet the ergonomic quality. Therefore, this research is to investigate the preferred driving posture of Malaysian driver in both sedan and MPV type of car. Sixty two subjects (32 males and 30 females) aged between 17-60 years old were selected to simulate the comfortable driving posture using mock-ups of sedan car and MPV. Measurements based on SAE J1100 vehicle package design geometry were carried out for each subject. Result shows slight differences in the range of posture angle between the two types of vehicles, the posture joint angle in MPV is slightly smaller as compared to those of sedan car. The range postural angles for Malaysian driver population also is slightly smaller compare to Caucasian people especially on lower body portion such as knee angle, hip angle and ankle angle. These angles are due to the body stature and body segment length in which the population of Malaysia have shorter thighs and legs than those in Europe and America.